YouTube as a source of chronic obstructive pulmonary disease patient education: A social media content analysis. (May 2014) - Stellefson, Michael; Chaney, Beth; Ochipa, Kathleen; Chaney, Don; Haider, Zeerak; Hanik, Bruce; Chavarria, Enmanuel; Bernhardt, Jay M.
The aim of the present study is to conduct a social media content analysis of chronic obstructive pulmonary disease (COPD) patient education videos on YouTube. A systematic search protocol was used to locate 223 videos. Two independent coders evaluated each video to determine topics covered, media source(s) of posted videos, information quality as measured by HONcode guidelines for posting trustworthy health information on the Internet, and viewer exposure/engagement metrics. Over half the videos ( n = 113, 50.7%) included information on medication management, with far fewer videos on smoking cessation ( n = 40, 17.9%). Most videos were posted by a health agency or organization ( n = 128, 57.4%), and the majority of videos were rated as high quality ( n = 154, 69.1%). HONcode adherence differed by media source (Fisher's exact test = 20.52, p = 0.01), however with user-generated content receiving the lowest quality scores. Overall level of user engagement as measured by number of "likes, " "favorites, " "dislikes, " and user comments was low (median range = 0–3, interquartile range = 0–16) across all sources of media. Study findings suggest that COPD education via YouTube has the potential to reach and inform patients; however, existing video content and quality varies significantly. Future interventions should help direct individuals with COPD to engage with high-quality patient education videos on YouTube that are posted by reputable health organizations and qualified medical professionals. Patients should be educated to avoid and/or critically view low-quality videos posted by individual YouTube users who are not health professionals.